Effect of the Composition of Lytic Bacteriophages of P. aeruginosa Formation and Destruction of Bacterial Biofilms - O. A. Polygach; A. N. Dabizheva; N. N. Voroshilova (Эпидемиология и вакцинопрофилактика)
Relevance. Biofilms of bacteria, in particular, pathogens of purulent-septic and enteral diseases, play an important role in the development of the infectious process, resulting in 60–70% of its chronic and recurrent forms. About 60% of nosocomial infections are caused by bacterial biofilms. In biofilms, the bacteria themselves make up only 5–35% of its total mass, the rest is an extracellular polymer matrix consisting of exopolysaccharides, DNA and proteins, which prevents the penetration of antimicrobial agents into biofilms. Resistance of bacteria in biofilms to antibiotics is 10–1000 times higher than the established concentrations for planktonic bacterial cells. The permeability in biofilms of different antibiotics differs. Bacteria P. aeruginosa have a high, as well as rapidly acquired resistance to most antibiotics, as well as the ability to form biofilms in the foci of inflammation.Goal of the study are a comparative study of the antibacterial activity of antibiotics and the bacteriophage composition of lytic groups of KMV-likevirus, PB-1 likevirus, N4-likevirus and phiKZ-likevirus against plankton cultures of clinical and hospital strains of P. aeruginosa, detection and study of the frequency of biofilm formation by bacteria P. aeruginosa and the preventive action of lytic bacteriophage compositions on them, as well as its ability to destroy bacterial biofilms.Materials and methods. The object of the study was the composition of bacteriophages of P. aeruginosa isolated from various sources of the external environment consisting of strains of bacteriophages of lytic groups KMV (PaUfa-1), PB-1(PaUfa-4), N4(PaUfa -3, 6, 7) and phiKZ(PaUfa-15)-like viruses, which do not contain genes for drug resistance, lysogenicity and toxigenicity, at a concentration of 5 x 107 PFU/ ml, analogous to phage concentration in therapeutic and prophylactic preparations of bacteriophages and 277 clinical and hospital strains of P. aeruginosa bacteria, allocated (2016-2017), in the cities of Moscow, Voronezh, Volgograd, Nizhny Novgorod, Krasnodar, St. Petersburg.Results and discussion. A study of the sensitivity of 277 clinical and hospital strains of P. aeruginosa bacteria to various groups of antibiotics showed that it is within the range of 53.5–80%. The width of the spectrum of antibacterial activity of the composition of bacteriophages of P. aeruginosa lytic groups CMV (PaUfa -1), PB-1(PaUfa -4), N4(PaUfa -3, 6, 7) and phiKZ(PaUfa -15)-likevirus planktonic cultures of hospital and clinical strains, was 89.97% (from 82 to 100%). Of the 42 clinical strains of P. aeruginosa bacteria, 33 strains (78.6%) formed biofilms, the remaining 9 strains showed less pronounced biofilm formation. After preliminary preventive treatment with a composition of bacteriophages of biofilm of strains of P. aeruginosa bacteria, 64.3% of them did not form of biofilm, in 35.7% of strains this ability decreased by 92.0–96.8%. The composition of the lytic bacteriophages KMV (PaUfa-1), PB-1(PaUfa-4), N4(PaUfa-3, 6, 7) and phiKZ(PaUfa-15)-ikevirus, even in a single treatment, destroyed biofilms of various strains P. aeruginosa with destruction from 23 to 100%. High antibacterial activity (an average of 89.97%) of the composition of the lytic bacteriophages P. aeruginosa KMV(PaUfa-1), PB-1(PaUfa-4), N4(PaUfa-3, 6, 7) and phiKZ(PaUfa-15)-like virus in the plankton cultures of P. aeruginosa bacteria falls insignificantly in biofilms (0–77.0%), the activity of antibiotics in biofilms is reduced by 10–1000 or more (decrease in penetration by 90.0–99,9999%).Conclusion. The composition of lytic bacteriophages exerts not only an antibacterial effect on planktonic cultures, but also acts proactively on the formation of bacterial biofilms and destroys them. The obtained data confirm the expediency of using P. aeruginosa bacteriophage preparations for the treatment and prevention of purulent-septic and enteral diseases of the synaeconomic etiology according to clinical and epidemiological indications.